Pengaruh stres kerja dan social support terhadap job satisfaction pada masa transisi kembali work from office (WFO) - Muhaimin, Yahya (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine and explain the effect of work stress moderated by social support on the job satisfaction of teachers and administrative staff at Al-Chusnaini Islamic Elementary School during the transition back to work from the office (WFO) since the COVID-19 pandemic. Respondents consisted of 57 people, then 51 people were used as samples. This quantitative study used simple random sampling to collect samples through questionnaires, interviews, and literature studies. This research uses Partial Least Square (PLS) analysis method with Structural Equation Modeling (SEM) technique, Microsoft Excel and SmartPLS 3.0 software to test the hypothesis. Based on the results of the analysis, it is known that work stress has a negative and significant effect on job satisfaction, and social support does not moderate job stress on job satisfaction because the stress level felt by teachers and administrative staff is not acute. However, social support has a significant effect on the job satisfaction of teachers and administrative staff of Al-Chusnaini Islamic Elementary School.